Asymptotic expansions for a natural generalization of the classical renewal theory - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкевичене. Асимптотические разложения для обобщенного процесса восстановления A. Aleškevičienė. Asimptotiniai išdėstymai apibendrintam atstatymo procesui